The Mazotos Shipwreck: preliminary results of the hull analysis - Demesticha, Stella; de Juan, Carlos (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
The 4th century BC shipwreck of Mazotos lies at -44 m off the south coast of Cyprus. Archaeological work on the site started in 2007 by a team of the University of Cyprus and is still in progress. After eight excavation seasons a good part of the hull has been unburied, mainly at the fore part of the ship. Evidence thus far suggests that it was a round bottom ship, fastened with pegged mortise and tenons. Some distinctive features, such as the round bottom profile of the hull, the framing pattern, and the presence of tetrahedral recesses at the bow extremity, open the question of the ship’s broader technological context, and underscore its important contribution to our knowledge on shipbuilding traditions in the eastern Mediterranean during the Classical period.